The BRICS Plus Cooperation in International Organizations: Prospects for Reshaping the Global Agenda - Arapova, Ekaterina Y. (Animo Repository, 2021)
The research is based on the Russian approach to implementing the BRICS Plus concept. The “BRICS Plus Circle” could unite the members of the five integration blocks, driven by the BRICS countries, which are mainly developing countries. These countries call for the creation of a more balanced global architecture based on the principles of non-discrimination, equal access to resources, and their fair distribution. Multilateral cooperation in the Bretton Woods institutions (the WTO, IMF, and the World Bank) may become one of the main modalities of the BRICS Plus interaction. In this regard, the paper aims to analyze the prospects for such cooperation and the potential instruments and mechanisms for maintaining a collective position. The authors conclude that the creation of a multilateral coalition of the BRICS Plus countries in the WTO could contribute to the reshaping of the WTO agenda, strengthening opposition to rising trade protectionism from the advanced economies, as well as advocating a shift from discussing trade facilitation and liberalization issues towards such new issues as e-commerce and investment facilitation. The cumulative BRICS Plus vision of IMF reform may include expanding the use of the IMF’s SDRs, increasing the set of reserve currencies, expanding the basket of currencies that form the basis for SDR valuation to include currencies of all major economies, and including GDP as a factor in currency selection for the SDR. The BRICS Plus bloc may help shift the World Bank’s agenda due to its close cooperation with the NDB and the AIIB.